PENGEMBANGAN BAHAN AJAR PEMBELAJARAN BERASIS OLAH PIKIR DI SEKOLAH DASAR - Indri Anugraheni; Firosalia Kristin; Gamaliel Septian Airlanda (INVENTA: Jurnal Pendidikan Guru Sekolah Dasar, 2018)
The purpose of this research is to develop teaching materials based on thought. The teaching materials that are developed are mathematics teaching materials and teaching materials of Social Sciences (IPS). This type of research is development research. Data analysis techniques used in this study by validation of the instrument in accordance with the validation criteria of instructional instruments and then describe the results of data analysis. The product resulting from this development research is the Character Based Mathematics Instruction Tool in Grade 4 which is in the Good category and the Mathematics Teaching Material product is in the good category and the Science-Based Social Science (IPS) materials based on Thinking in grade 4 are in the category Good.